Ant and termite diversity in Indonesian oil palm plantation: Investigating the effect of natural habitat existence - Akhmad Rizali; Sri Karindah; Anna Windari; Bambang Rahardjo; Nurindah Nurindah; Bandung Sahari (Society for Indonesian Biodiversity, 2020)
Abstract. Rizali A, Karindah S, Windari A, Rahardjo BT, Nurindah, Sahari B. 2020. Ant and termite diversity in Indonesian oil palm plantation: Investigating the effect of natural habitat existence. Biodiversitas 21: 1326-1331. Natural habitat existence in oil palm plantation has high conservation value and plays an important role in maintaining biodiversity. However, different taxa may have different responses to the presence of natural habitats. This research was aimed to investigate the effect of natural habitat existence on ant and termite diversity in oil palm plantation. The field research was conducted in oil palm plantation located in Central Kalimantan, Indonesia. Twelve plots of oil palm plantation with different habitat characteristics were selected. Ants and termites were sampled using hand collection in six subplots for each plot. In total, 38 species of ants and 9 species of termites were collected from all research areas. The results showed that the area of natural habitats and the distance of oil palm field to natural habitats affected the diversity of termites in the oil palm plantation, but ant diversity did not show to be affected by the same conditions. Based on the generalized linear model, the area of natural habitats in the oil palm plantation had a negative relationship with the diversity of termites. In conclusion, the termite species community is more affected by natural habitats than ants in oil palm plantation.